Legal Protection for Local Communities against Dominance of Foreign Investors in Project Capital investment - Radea Respati Paramudhita (SEAN Institute, 2025)
The phenomenon of increasing foreign investment often creates unequal legal relations between investors and local communities, particularly regarding land ownership, economic rights, and environmental sustainability. This study aims to analyze the form and effectiveness of legal protection for local communities against foreign investor domination in investment projects in Indonesia. The research method used is normative juridical with a statutory and conceptual approach, supported by case studies in several regions that are foreign investment locations. Data were obtained through a literature review of laws and regulations, legal literature, and relevant court decisions. The results of this study indicate that legal protection for local communities against foreign investor domination in investment projects in Indonesia is still not optimal, despite the existence of an adequate legal framework. The implementation of Law Number 25 of 2007 concerning Investment and Law Number 32 of 2009 concerning Environmental Protection and Management has not fully been able to ensure a balance between economic interests and community rights. The study found that various violations still occur, such as environmental pollution, eviction of customary land, and social marginalization, which are consequences of weak supervision and law enforcement. Furthermore, foreign investor dominance is reinforced by imbalances in economic and political power, a lack of information transparency, and limited public participation in the investment licensing and oversight process. However, there are opportunities to strengthen legal protection through capacity building of supervisory institutions, strengthening inter-agency coordination, implementing strict sanctions for violations, and active public involvement in every investment stage.